Training for Coherence Formation When Learning From Text and Picture and the Interplay With Learners’ Prior Knowledge - Seufert, Tina (Frontiers in Psychology, 2019)
Learning with text and pictures requires learners to integrate the given information into one coherent mental representation. Since learners often fail to integrate text and pictures, the study investigates the effects of a training for text processing strategies, picture processing strategies and strategies to map text and picture onto each other. It was assumed that learners’ prior knowledge would affect the effects of such a training with more beneficial effects for learners with high prior knowledge. The training comprised an introduction on how to process, integrate and reflect on texts and pictures with an additional training phase of three weeks. The study (N = 30) analyzed the effects of the training with regard to recall and comprehension performance in contrast to an alternative training program which was not related to text-picture integration. A regression analysis showed that the integration training was not overall beneficial but only for learners with increased levels of prior knowledge. Hence, training for coherence formation is beneficial for learning only when adequate knowledge structures are available to conduct the recommended steps of understanding and integrating text and picture.